A Genome-Wide RNAi Screen for Enhancers of a Germline Tumor Phenotype Caused by Elevated GLP-1/Notch Signaling in Caenorhabditis elegans. Issue 12 (1st December 2020) - Dalfó, Diana; Ding, Yanhui; Liang, Qifei; Fong, Alex; Cipriani, Patricia Giselle; Piano, Fabio; Zheng, Jialin C; Qin, Zhao; Hubbard, E Jane Albert
Abstract: Stem cells are tightly controlled in vivo . Both the balance between self-renewal and differentiation and the rate of proliferation are often regulated by multiple factors. The Caenorhabditis elegans hermaphrodite germ line provides a simple and accessible system for studying stem cells in vivo . In this system, GLP-1 /Notch activity prevents the differentiation of distal germ cells in response to ligand production from the nearby distal tip cell, thereby supporting a stem cell pool. However, a delay in germline development relative to somatic gonad development can cause a pool of undifferentiated germ cells to persist in response to alternate Notch ligands expressed in the proximal somatic gonad. This pool of undifferentiated germ cells forms a proximal tumor that, in adulthood, blocks the oviduct. This type of "latent niche"-driven proximal tumor is highly penetrant in worms bearing the temperature-sensitive weak gain-of-function mutation glp-1 ( ar202 ) at the restrictive temperature. At the permissive temperature, few worms develop tumors. Nevertheless, several interventions elevate the penetrance of proximal tumor formation at the permissive temperature, including reduced insulin signaling or the ablation of distal-most sheath cells. To systematically identify genetic perturbations that enhance proximal tumor formation, we sought genes that, upon RNAi depletion, elevate the percentage of worms bearing proximal germline tumors in glp-1 ( ar202 ) at the permissive temperature. We identified 43 genes representing a variety of functional classes, the most enriched of which is "translation". Some of these genes also influence the distal germ line, and some are conserved genes for which genetic interactions with Notch were not previously known in this system.